2012
DOI: 10.6001/actamedica.v19i2.2312
|View full text |Cite
|
Sign up to set email alerts
|

Features of the sexual life during pregnancy

Abstract: Background. The aim of our study was to evaluate Vilnius and Vilnius Region women's knowledge about sexual intercourse during pregnancy.Materials and methods. The study included 94 women who were in the Center Affiliate of VUH Santariskiu Clinics after delivery. The women were interviewed using a questionnaire. They were divided in three groups by levels of education.Results. The study showed that 83% of pregnant women had sexual intercourse during pregnancy. 55.1% had coitus several times a month. The first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…Jelena Isajeva et al in their study founded that 52.6% (n = 41) had frequent sexual intercourse during the first trimester, 24.4% (n = 19) had it during the second trimester and only a small amount of the women had it during the third trimester. The majority of the authors indicate a decrease in the frequency of sexual intercourse during pregnancy [5]. In this study an increase in the number of women who did not have any sexual intercourse during a week in the first quarter can be noticed.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Jelena Isajeva et al in their study founded that 52.6% (n = 41) had frequent sexual intercourse during the first trimester, 24.4% (n = 19) had it during the second trimester and only a small amount of the women had it during the third trimester. The majority of the authors indicate a decrease in the frequency of sexual intercourse during pregnancy [5]. In this study an increase in the number of women who did not have any sexual intercourse during a week in the first quarter can be noticed.…”
Section: Discussionmentioning
confidence: 49%
“…Myths about sex during pregnancy harming fetus and leading to preterm labor or miscarriage are very strong factors releasing fear and leading to avoidance of sexual contact during gestation [4]. Different studies showed that 86% -100% of couples remained sexually active during pregnancy but experienced reduction in sexual activity, especially in the third trimester [5]. This is one of the largest studies about the impact of pregnancy in sexual life using a validated inventory.…”
Section: Introductionmentioning
confidence: 99%
“… 1 This transition period affects the sexual orientation and sexual life of couples through creating physical, emotional, and psychological changes, along with sociocultural factors 2 , 3 and religious beliefs. 2 4 Marital and sexual relations during pregnancy change considerably as a result of several physical and psychological changes. In other words, during transition from the role of a spouse to that of a parent, the relationship between a couple changes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study by Malewitz [18], sexuality in pregnancy to Polish couples means quite a stimulus to search for new ways of pleasing each other in love play. Their research makes it evident that experiencing sexual satisfaction by pregnant women improves their self-esteem, facilitates mutual relationship between partners and tightens the marital bond [18].…”
Section: Social Cultural Factors and Norms Fears And Mythsmentioning
confidence: 99%
“…Sometimes couples are not aware of alterations in sexual functioning in pregnancy and might be frightened or having a hard time adapting to changes. Many studies exploring sexual functions of pregnant women [9][10][11][12][13][14][15][16][17][18] identified that couples do not receive adequate (if any) information about changes in their sexual functioning. Women or couples are also not always comfortable in raising sexual concerns [21].…”
Section: Counsellingmentioning
confidence: 99%